Somatic embryogenesis in higher plants - Normah, M.N.; Rohani, E.R.; Mohamed-Hussein, Z.A. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Somatic embryogenesis is an illustration of plant totipotency. There are many factors involved in causing development switching during somatic embryogenesis. These include combination of plant growth regulators, media, pretreatments and culture environments, which relate to various molecular events encompassing gene expression and signal transduction pathways.The present review collates information on various aspects of somatic embryogenesis focusing on genes involved, proteins and metabolites that have been identified during the last few years. Future work on integrating various data on somatic embryogenesis using the computational or systems biology approach is suggested.